Correction to: Genetic structure and geneflow of crowned bullfrogs (Hoplobatrachus occipitalis) across ecological zones in Southwestern Nigeria - Oluwakayode Michael Coker; Isaac Overcast; Rayna C. Bell (Conservation Genetics, 2026)

Genetic structure and geneflow of crowned bullfrogs (Hoplobatrachus occipitalis) across ecological zones in Southwestern Nigeria - Oluwakayode Michael Coker; Isaac Overcast; Rayna C. Bell (Conservation Genetics, 2026)

Pleistocene Glaciation Drove Shared Population Coexpansion in Eastern North American Snakes - Sean Harrington; Isaac Overcast; Edward A. Myers; Frank T. Burbrink (Molecular Ecology, 2025)
Glacial cycles during the Pleistocene had profound impacts on local environments and climatic conditions. In North America, some regions that currently support diverse biomes were entirely covered by ice sheets, while other regions were environmentally unsuitable for the organisms that live there now. Organisms that occupy these regions in the present day must have expanded or dispersed into these regions since the last glacial maximum, leading to the possibility that species with similar geographic distributions may show temporally concordant population size changes associated with these warming trends. We examined 17 lineages from 9 eastern North American snake species and species complexes to test for a signal of temporally concordant coexpansion using a machine learning approach. We found that the majority of lineages show population size increases towards the present, with evidence for coexpansion in five out of fourteen lineages, while expansion in others was idiosyncratic. We also examined relationships between genetic distance and current environmental predictors and showed that genomic responses to environmental predictors are not consistent among species. We, therefore, conclude that Pleistocene warming resulted in population size increases in most eastern North American snake species, but variation in environmental preferences and other species‐specific traits results in variance in the exact timing of expansion.

Insights into Ecological & Evolutionary Processes via community metabarcoding - Rosemary G. Gillespie; Holly M. Bik; Michael J. Hickerson; Henrik Krehenwinkel; Isaac Overcast; Andrew J. Rominger (Molecular Ecology, 2023)

Inferring the ecological and evolutionary determinants of community genetic diversity - Isaac Overcast; Víctor Noguerales; Emmanouil Meramveliotakis; Carmelo Andújar; Paula Arribas; Thomas J. Creedy; Brent C. Emerson; Alfried P. Vogler; Anna Papadopoulou; Hélène Morlon (Molecular Ecology, 2023)
Understanding the relative contributions of ecological and evolutionary processes to the structuring of ecological communities is needed to improve our ability to predict how communities may respond to future changes in an increasingly human‐modified world. Metabarcoding methods make it possible to gather population genetic data for all species within a community, unlocking a new axis of data to potentially unveil the origins and maintenance of biodiversity at local scales. Here, we present a new eco‐evolutionary simulation model for investigating community assembly dynamics using metabarcoding data. The model makes joint predictions of species abundance, genetic variation, trait distributions and phylogenetic relationships under a wide range of parameter settings (e.g. high speciation/low dispersal or vice versa) and across a range of community states, from pristine and unmodified to heavily disturbed. We first demonstrate that parameters governing metacommunity and local community processes leave detectable signatures in simulated biodiversity data axes. Next, using a simulation‐based machine learning approach we show that neutral and non‐neutral models are distinguishable and that reasonable estimates of several model parameters within the local community can be obtained using only community‐scale genetic data, while phylogenetic information is required to estimate those describing metacommunity dynamics. Finally, we apply the model to soil microarthropod metabarcoding data from the Troodos mountains of Cyprus, where we find that communities in widespread forest habitats are structured by neutral processes, while high‐elevation and isolated habitats act as an abiotic filter generating non‐neutral community structure. We implement our model within the ibiogen R package, a package dedicated to the investigation of island, and more generally community‐scale, biodiversity using community‐scale genetic data.

Collective and harmonized high throughput barcoding of insular arthropod biodiversity: Toward a Genomic Observatories Network for islands - Brent C. Emerson; Paulo A. V. Borges; Pedro Cardoso; Peter Convey; Jeremy R. deWaard; Evan P. Economo; Rosemary G. Gillespie; Susan Kennedy; Henrik Krehenwinkel; Rudolf Meier; George K. Roderick; Dominique Strasberg; et al. (Molecular Ecology, 2023)
Current understanding of ecological and evolutionary processes underlying island biodiversity is heavily shaped by empirical data from plants and birds, although arthropods comprise the overwhelming majority of known animal species, and as such can provide key insights into processes governing biodiversity. Novel high throughput sequencing (HTS) approaches are now emerging as powerful tools to overcome limitations in the availability of arthropod biodiversity data, and hence provide insights into these processes. Here, we explored how these tools might be most effectively exploited for comprehensive and comparable inventory and monitoring of insular arthropod biodiversity. We first reviewed the strengths, limitations and potential synergies among existing approaches of high throughput barcode sequencing. We considered how this could be complemented with deep learning approaches applied to image analysis to study arthropod biodiversity. We then explored how these approaches could be implemented within the framework of an island Genomic Observatories Network (iGON) for the advancement of fundamental and applied understanding of island biodiversity. To this end, we identified seven island biology themes at the interface of ecology, evolution and conservation biology, within which collective and harmonized efforts in HTS arthropod inventory could yield significant advances in island biodiversity research.

Community metabarcoding reveals the relative role of environmental filtering and spatial processes in metacommunity dynamics of soil microarthropods across a mosaic of montane forests - Víctor Noguerales; Emmanouil Meramveliotakis; Adrián Castro‐Insua; Carmelo Andújar; Paula Arribas; Thomas J. Creedy; Isaac Overcast; Hélène Morlon; Brent C. Emerson; Alfried P. Vogler; Anna Papadopoulou (Molecular Ecology, 2023)
Disentangling the relative role of environmental filtering and spatial processes in driving metacommunity structure across mountainous regions remains challenging, as the way we quantify spatial connectivity in topographically and environmentally heterogeneous landscapes can influence our perception of which process predominates. More empirical data sets are required to account for taxon‐ and context‐dependency, but relevant research in understudied areas is often compromised by the taxonomic impediment. Here we used haplotype‐level community DNA metabarcoding, enabled by stringent filtering of amplicon sequence variants (ASVs), to characterize metacommunity structure of soil microarthropod assemblages across a mosaic of five forest habitats on the Troodos mountain range in Cyprus. We found similar β diversity patterns at ASV and species (OTU, operational taxonomic unit) levels, which pointed to a primary role of habitat filtering resulting in the existence of largely distinct metacommunities linked to different forest types. Within‐habitat turnover was correlated to topoclimatic heterogeneity, again emphasizing the role of environmental filtering. However, when integrating landscape matrix information for the highly fragmented Quercus alnifolia habitat, we also detected a major role of spatial isolation determined by patch connectivity, indicating that stochastic and niche‐based processes synergistically govern community assembly. Alpha diversity patterns varied between ASV and OTU levels, with OTU richness decreasing with elevation and ASV richness following a longitudinal gradient, potentially reflecting a decline of genetic diversity eastwards due to historical pressures. Our study demonstrates the utility of haplotype‐level community metabarcoding for characterizing metacommunity structure of complex assemblages and improving our understanding of biodiversity dynamics across mountainous landscapes worldwide.

Towards a genetic theory of island biogeography: Inferring processes from multidimensional community‐scale data - Isaac Overcast; Guillaume Achaz; Robin Aguilée; Carmelo Andújar; Paula Arribas; Thomas J. Creedy; Evan P. Economo; Rampal S. Etienne; Rosemary Gillespie; Claire Jacquet; Flora Jay; Susan Kennedy; et al. (Global Ecology and Biogeography, 2023)
Background MacArthur and Wilson's theory of island biogeography has been a foundation for obtaining testable predictions from models of community assembly and for developing models that integrate across scales and disciplines. Historically, however, these developments have focused on integration across ecological and macroevolutionary scales and on predicting patterns of species richness, abundance distributions, trait data and/or phylogenies. The distribution of genetic variation across species within a community is an emerging pattern that contains signatures of past population histories, which might provide an historical lens for the study of contemporary communities. As intraspecific genetic diversity data become increasingly available at the scale of entire communities, there is an opportunity to integrate microevolutionary processes into our models, moving towards development of a genetic theory of island biogeography. Motivation/goal We aim to promote the development of process‐based biodiversity models that predict community genetic diversity patterns together with other community‐scale patterns. To this end, we review models of ecological, microevolutionary and macroevolutionary processes that are best suited to the creation of unified models, and the patterns that these predict. We then discuss ongoing and potential future efforts to unify models operating at different organizational levels, with the goal of predicting multidimensional community‐scale data including a genetic component. Main conclusions Our review of the literature shows that despite recent efforts, further methodological developments are needed, not only to incorporate the genetic component into existing island biogeography models, but also to unify processes across scales of biological organization. To catalyse these developments, we outline two potential ways forward, adopting either a top‐down or a bottom‐up approach. Finally, we highlight key ecological and evolutionary questions that might be addressed by unified models including a genetic component and establish hypotheses about how processes across scales might impact patterns of community genetic diversity.

Drivers of unique and asynchronous population dynamics in Malagasy herpetofauna - Arianna Kuhn; Marcelo Gehara; Mamy S. M. Andrianarimalala; Nirhy Rabibisoa; Bernard Randriamahatantsoa; Isaac Overcast; Christopher J. Raxworthy; Sara Ruane; Frank T. Burbrink (Journal of Biogeography, 2022)
Aim A long history of isolation coupled with complex landscapes makes Madagascar ideal for exploring the historical factors that have shaped patterns of population diversity and endemism. Many species‐level studies have suggested Late Quaternary climate change may have influenced population dynamics in the tropics, but unique biomes and individual species properties may have driven idiosyncratic responses to these shifts. Here, we use community‐scale population genetic data to investigate the impact of Quaternary climate cycles on shared demographic response and investigate the contributions of both biotic and abiotic factors which shape these demographic trajectories. Location Madagascar. Taxon Reptiles and Amphibians. Methods Using community‐scale population genetic data, we implement a hierarchical approximate Bayesian computation approach to evaluate the degree of synchronous population expansion during glacial cycles across herpetofaunal assemblages both within and across discrete biomes and taxonomic groups. We use Bayesian model averaging to identify intrinsic and extrinsic conditions predictive of individualistic demographic change. Results We find that demographic responses are not uniform across groups, with more than 50% of all populations showing signal of recent expansion. Our explanatory models indicate species occupying narrow elevational ranges had a higher probability of expansion, while amphibian assemblages showed higher genetic diversity and greater departures from population neutrality. Expansion events were largely asynchronous, with coexpansion found in less than half of all populations. Exceptionally, 69%–74% of all humid‐restricted populations coexpanded during the start of the Last Glacial Period at around 100 kya, supporting the hypothesis of a more extensive humid forest cover for Madagascar during this time. Main conclusions We show that differences in life history and regional biogeography have contributed to patterns of richness and endemism found across Madagascar, and historical connectivity across humid forests has been an important factor in shaping present‐day diversity and endemism on Madagascar, particularly for amphibians.

Complex genetic patterns and distribution limits mediated by native congeners of the worldwide invasive red‐eared slider turtle - Sayra Espindola; Ella Vázquez‐Domínguez; Miguel Nakamura; Luis Osorio‐Olvera; Enrique Martínez‐Meyer; Edward A. Myers; Isaac Overcast; Brendan N. Reid; Frank T. Burbrink (Molecular Ecology, 2022)
Non‐native (invasive) species offer a unique opportunity to study the geographical distribution and range limits of species, wherein the evolutionary change driven by interspecific interactions between native and non‐native closely related species is a key component. The red‐eared slider turtle, Trachemys scripta elegans (TSE), has been introduced and successfully established worldwide. It can coexist with its native congeners T . cataspila , T . venusta and T . taylori in Mexico. We performed comprehensive fieldwork, executed a battery of genetic analyses and applied a novel species distribution modelling approach to evaluate their historical lineage relationships and contemporary population genetic patterns. Our findings support the historical common ancestry between native TSE and non‐native (TSE alien ), while also highlighting the genetic differentiation of the exotic lineage. Genetic patterns are associated with their range size/endemism gradient; the microendemic T . taylori showed significant reduced genetic diversity and high differentiation, whereas TSE alien showed the highest diversity and signals of population size expansion. Counter to our expectations, lower naturally occurring distribution overlap and little admixture patterns were found between TSE and its congeners, exhibiting reduced gene flow and clear genetic separation across neighbouring species despite having zones of contact. We demonstrate that these native Trachemys species have distinct climatic niche suitability, probably preventing establishment of and displacement by the TSE alien . Moreover, we found major niche overlap between TSE alien and native species worldwide, supporting our prediction that sites with closer ecological optima to the invasive species have higher establishment risk than those that are closer to the niche‐centre of the native species.

Connecting high‐throughput biodiversity inventories: Opportunities for a site‐based genomic framework for global integration and synthesis - Paula Arribas; Carmelo Andújar; Martin I. Bidartondo; Kristine Bohmann; Éric Coissac; Simon Creer; Jeremy R. deWaard; Vasco Elbrecht; Gentile F. Ficetola; Marta Goberna; Susan Kennedy; Henrik Krehenwinkel; et al. (Molecular Ecology, 2021)
High‐throughput sequencing (HTS) is increasingly being used for the characterization and monitoring of biodiversity. If applied in a structured way, across broad geographical scales, it offers the potential for a much deeper understanding of global biodiversity through the integration of massive quantities of molecular inventory data generated independently at local, regional and global scales. The universality, reliability and efficiency of HTS data can potentially facilitate the seamless linking of data among species assemblages from different sites, at different hierarchical levels of diversity, for any taxonomic group and regardless of prior taxonomic knowledge. However, collective international efforts are required to optimally exploit the potential of site‐based HTS data for global integration and synthesis, efforts that at present are limited to the microbial domain. To contribute to the development of an analogous strategy for the nonmicrobial terrestrial domain, an international symposium entitled “Next Generation Biodiversity Monitoring” was held in November 2019 in Nicosia (Cyprus). The symposium brought together evolutionary geneticists, ecologists and biodiversity scientists involved in diverse regional and global initiatives using HTS as a core tool for biodiversity assessment. In this review, we summarize the consensus that emerged from the 3‐day symposium. We converged on the opinion that an effective terrestrial Genomic Observatories network for global biodiversity integration and synthesis should be spatially led and strategically united under the umbrella of the metabarcoding approach. Subsequently, we outline an HTS‐based strategy to collectively build an integrative framework for site‐based biodiversity data generation.

A topoclimate model for Quaternary insular speciation - Víctor García‐Olivares; Jairo Patiño; Isaac Overcast; Antonia Salces‐Castellano; Unai López de Heredia; Fernando Mora‐Márquez; Antonio Machado; Michael J. Hickerson; Brent C. Emerson (Journal of Biogeography, 2019)
Aim Understanding the drivers of speciation within islands is key to explain the high levels of invertebrate diversification and endemism often observed within islands. Here, we propose an insular topoclimate model for Quaternary diversification (ITQD), and test the general prediction that, within a radially eroded conical island, glacial climate conditions facilitate the divergence of populations within species across valleys. Location Gran Canaria, Canary Islands. Taxon The Laparocerus tessellatus beetle species complex (Coleoptera, Curculionidae). Methods We characterize individual‐level genomic relationships using single nucleotide polymorphisms produced by double‐digest restriction site associated DNA sequencing (ddRAD‐seq). A range of parameter values were explored in order to filter our data. We assess individual relatedness, species boundaries, demographic history and spatial patterns of connectivity. Results The total number of ddRAD‐seq loci per sample ranges from 4,576 to 512, with 11.12% and 4.84% of missing data respectively, depending on the filtering parameter combination. We consistently infer four genetically distinct ancestral populations and two presumed cases of admixture, one of which is largely restricted to high altitudes. Bayes factor delimitation support the hypothesis of four species, which is consistent with the four inferred ancestral gene pools. Landscape resistance analyses identified genomic relatedness among individuals in two out of the four inferred species to be best explained by annual precipitation during the last glacial maximum rather than geographic distance. Main conclusions Our data reveal a complex speciation history involving population isolation and admixture, with broad support for the ITQD model here proposed. We suggest that further studies are needed to test the generality of our model, and enrich our understanding of the evolutionary process in island invertebrates. Our results demonstrate the power of ddRAD‐seq data to provide a detailed understanding of the temporal and spatial dynamics of insular biodiversity.

Unifying macroecology and macroevolution to answer fundamental questions about biodiversity - Brian J. McGill; Jonathan M. Chase; Joaquín Hortal; Isaac Overcast; Andrew J. Rominger; James Rosindell; Paulo A. V. Borges; Brent C. Emerson; Rampal S. Etienne; Michael J. Hickerson; D. Luke Mahler; Francois Massol; et al. (Global Ecology and Biogeography, 2019)
The study of biodiversity started as a single unified field that spanned both ecology and evolution and both macro and micro phenomena. But over the 20th century, major trends drove ecology and evolution apart and pushed an emphasis towards the micro perspective in both disciplines. Macroecology and macroevolution re‐emerged as self‐consciously distinct fields in the 1970s and 1980s, but they remain largely separated from each other. Here, we argue that despite the challenges, it is worth working to combine macroecology and macroevolution. We present 25 fundamental questions about biodiversity that are answerable only with a mixture of the views and tools of both macroecology and macroevolution.

An integrated model of population genetics and community ecology - Isaac Overcast; Brent C. Emerson; Michael J. Hickerson (Journal of Biogeography, 2019)
Aim Quantifying abundance distributions is critical for understanding both how communities assemble, and how community structure varies through time and space, yet estimating abundances requires considerable investment in fieldwork. Community‐level population genetic data potentially offer a powerful way to indirectly infer richness, abundance and the history of accumulation of biodiversity within a community. Here we introduce a joint model linking neutral community assembly and comparative phylogeography to generate both community‐level richness, abundance and genetic variation under a neutral model, capturing both equilibrium and non‐equilibrium dynamics. Location Global. Methods Our model combines a forward‐time individual‐based community assembly process with a rescaled backward‐time neutral coalescent model of multi‐taxa population genetics. We explore general dynamics of genetic and abundance‐based summary statistics and use approximate Bayesian computation ( ABC ) to estimate parameters underlying the model of island community assembly. Finally, we demonstrate two applications of the model using community‐scale mt DNA sequence data and densely sampled abundances of an arachnid community on La Réunion. First, we use genetic data alone to estimate a summary of the abundance distribution, ground‐truthing this against the observed abundances. Then, we jointly use the observed genetic data and abundances to estimate the proximity of the community to equilibrium. Results Simulation experiments of our ABC procedure demonstrate that coupling abundance with genetic data leads to improved accuracy and precision of model parameter estimates compared with using abundance‐only data. We further demonstrate reasonable precision and accuracy in estimating a metric underlying the shape of the abundance distribution, temporal progress towards local equilibrium and several key parameters of the community assembly process. For the insular arachnid assemblage, we find the joint distribution of genetic diversity and abundance approaches equilibrium expectations, and that the Shannon entropy of the observed abundances can be estimated using genetic data alone. Main conclusions The framework that we present unifies neutral community assembly and comparative phylogeography to characterize the community‐level distribution of both abundance and genetic variation through time, providing a resource that should greatly enhance understanding of both the processes structuring ecological communities and the associated aggregate demographic histories.

Behavioural response to song and genetic divergence in two subspecies of white‐crowned sparrows ( Zonotrichia leucophrys ) - Sara E. Lipshutz; Isaac A. Overcast; Michael J. Hickerson; Robb T. Brumfield; Elizabeth P. Derryberry (Molecular Ecology, 2017)
Divergence in sexual signals may drive reproductive isolation between lineages, but behavioural barriers can weaken in contact zones. Here, we investigate the role of song as a behavioural and genetic barrier in a contact zone between two subspecies of white‐crowned sparrows ( Zonotrichia leucophrys ). We employed a reduced genomic data set to assess population structure and infer the history underlying divergence, gene flow and hybridization. We also measured divergence in song and tested behavioural responses to song using playback experiments within and outside the contact zone. We found that the subspecies form distinct genetic clusters, and demographic inference supported a model of secondary contact. Song phenotype, particularly length of the first note (a whistle), was a significant predictor of genetic subspecies identity and genetic distance along the hybrid zone, suggesting a close link between song and genetic divergence in this system. Individuals from both parental and admixed localities responded significantly more strongly to their own song than to the other subspecies song, supporting song as a behavioural barrier. Putative parental and admixed individuals were not significantly different in their strength of discrimination between own and other songs; however, individuals from admixed localities tended to discriminate less strongly, and this difference in discrimination strength was explained by song dissimilarity as well as genetic distance. Therefore, we find that song acts as a reproductive isolating mechanism that is potentially weakening in a contact zone between the subspecies. Our findings also support the hypothesis that intraspecific song variation can reduce gene flow between populations.

Isolation with asymmetric gene flow during the nonsynchronous divergence of dry forest birds - Jessica A. Oswald; Isaac Overcast; William M. Mauck; Michael J. Andersen; Brian Tilston Smith (Molecular Ecology, 2017)
Dry forest bird communities in South America are often fragmented by intervening mountains and rainforests, generating high local endemism. The historical assembly of dry forest communities likely results from dynamic processes linked to numerous population histories among codistributed species. Nevertheless, species may diversify in the same way through time if landscape and environmental features, or species ecologies, similarly structure populations. Here we tested whether six co‐distributed taxon pairs that occur in the dry forests of the Tumbes and Marañón Valley of northwestern South America show concordant patterns and modes of diversification. We employed a genome reduction technique, double‐digest restriction site‐associated DNA sequencing, and obtained 4407–7186 genomewide SNP s. We estimated demographic history in each taxon pair and inferred that all pairs had the same best‐fit demographic model: isolation with asymmetric gene flow from the Tumbes into the Marañón Valley, suggesting a common diversification mode. Overall, we also observed congruence in effective population size ( N e ) patterns where ancestral N e were 2.9–11.0× larger than present‐day Marañón Valley populations and 0.3–2.0× larger than Tumbesian populations. Present‐day Marañón Valley N e was smaller than Tumbes. In contrast, we found simultaneous population isolation due to a single event to be unlikely as taxon pairs diverged over an extended period of time (0.1–2.9 Ma) with multiple nonoverlapping divergence periods. Our results show that even when populations of codistributed species asynchronously diverge, the mode of their differentiation can remain conserved over millions of years. Divergence by allopatric isolation due to barrier formation does not explain the mode of differentiation between these two bird assemblages; rather, migration of individuals occurred before and after geographic isolation.